The Impact of Working Wife To implementation Of Rights and Obligations (Case Study in The City of Banjarmasin) - Nurul Udhiyati; Rahmat Fadillah (Sharia Journal and Education Center Publishing, 2023)
ABSTRACT This research was carried out by describing phenomena in the field found by wives who work excessively, so that time to be with the family is reduced, housework is sometimes neglected, including in terms of taking care of the needs of husbands and children, many children, the majority of whose mothers work, are not properly cared for. good because a mother is busy working so she doesn't have time to take care of and look after her child. This of course will have an impact on the rights and obligations as a wife, especially if the wife is working. This study used a qualitative research method using an analytical descriptive approach. The informants in this study are husband and wife who are resident in the city of Banjarmasin where the wife works to help earn a living. Data collection techniques are using observation, interviews, and documentation. The data analysis was carried out using stages such as data reduction, data display, and verification-conclusion. The results of this study the authors found: First, the background of the existence of a working wife is because the income earned by the husband in the household is not sufficient for daily needs so that the family's economic imbalance causes what happens in the family to make the wives also work. Second, the impact that occurs from having a wife who works is to have positive and negative impacts. The positive impact is helping the family's economy, lightening the husband's burden, the household becomes more prosperous, and as a manifestation of the wife's devotion to her husband. The negative impact is negligence in managing the household which requires the husband's consent and which interferes with the obligation to take care of the household and lack of time with the family. Keywords: Working Wife, Wife's Rights, Wife's Obligations ABSTRAK Penelitian ini dilakukan dengan mendeskripsikan fenomena di lapangan yang ditemukan istri yang bekerja secara berlebihan, sehingga waktu untuk bersama keluarga menjadi berkurang, pekerjaan rumah tangga pun terkadang terbengkalai, termasuk dalam hal mengurus kebutuhan suami dan anak, banyak anak yang mayoritas ibunya bekerja tidak terurus dengan baik karena seorang ibu yang sibuk bekerja sehingga tidak memiliki waktu untuk mengasuh dan menjaga anaknya. Hal ini tentu saja akan berdampak pada hak dan kewajiban sebagai seorang istri, apalagi jika istri bekerja. Penelitian ini menggunakan metode penelitian kualitatif dengan menggunakan pendekatan deskriptif analitis. Informan dalam penelitian ini adalah pasangan suami istri yang berdomisili di kota Banjarmasin dimana istri bekerja membantu mencari nafkah. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Analisis data dilakukan dengan menggunakan tahapan-tahapan seperti reduksi data, display data, dan verifikasi-kesimpulan. Hasil dari penelitian ini penulis menemukan: Pertama, latar belakang adanya istri yang bekerja adalah karena penghasilan yang diperoleh suami dalam rumah tangga tidak mencukupi kebutuhan sehari-hari sehingga ketidakseimbangan ekonomi keluarga menyebabkan apa yang terjadi di dalam keluarga membuat para istri juga ikut bekerja. Kedua, dampak yang terjadi dari adanya istri yang bekerja adalah memberikan dampak positif dan negatif. Dampak positifnya adalah membantu perekonomian keluarga, meringankan beban suami, rumah tangga menjadi lebih sejahtera, dan sebagai wujud bakti istri kepada suami. Dampak negatifnya adalah kelalaian dalam mengurus rumah tangga yang membutuhkan persetujuan suami dan mengganggu kewajiban mengurus rumah tangga serta kurangnya waktu bersama keluarga. Kata kunci: Istri Bekerja, Hak Istri, Kewajiban Istri